2018
DOI: 10.17294/2330-0698.1581
|View full text |Cite
|
Sign up to set email alerts
|

Identifying What Matters to Hysterectomy Patients: Postsurgery Perceptions, Beliefs, and Experiences

Abstract: These findings about perceptions, beliefs, and attitudes of women having undergone hysterectomy could support health care providers deliver patient-centered care. These results informed data collection for a prospective longitudinal cohort study that is now underway. The data suggest a need for increased education and empowerment in the decision making process, while expanding on information given for post-operative expectations and somatic changes that occur post-hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…The main ndings were a limited ability to make well-informed, independent decisions due to insu cient health literacy and a dependency on health professionals with insu cient information provided, as perceived by the participants. This is supported by previous studies including women after having had a hysterectomy, urging for more education prior to surgery (5). If convalescence was discussed in the consultation, the problems were expected to be understated.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The main ndings were a limited ability to make well-informed, independent decisions due to insu cient health literacy and a dependency on health professionals with insu cient information provided, as perceived by the participants. This is supported by previous studies including women after having had a hysterectomy, urging for more education prior to surgery (5). If convalescence was discussed in the consultation, the problems were expected to be understated.…”
Section: Discussionmentioning
confidence: 52%
“…Similarly, in a Norwegian study, persevering thoughts on not being a complete woman after hysterectomy was described if the sense of self was connected to the uterus (23). Women experiencing a sense of being incomplete after hysterectomy have been described in studies from different parts of the world (5,24).…”
Section: Discussionmentioning
confidence: 99%
“…Their experiences included anxiety, "secret keeping," isolation, shame, and ostracization. 11 Similar to the findings of Bossick et al regarding hysterectomy choices, 5 Dahlerus and colleagues, in their qualitative study of patients with advanced chronic kidney disease, found that these individuals wished more input into dialysis decisions. 13 Some had fear and lack of conveyed knowledge, if not explicit uncertainty.…”
mentioning
confidence: 52%
“…4 Finally, in their exploration of what outcomes matter most to hysterectomy patients, Bossick et al concluded that their collective data "suggest a need for increased education and empowerment in the decision-making process." 5 Several of the included participant quotes implied issues of uncertainty surrounding hysterectomy decisions. 5 It might be tempting to write off these concerns of uncertainty as merely a byproduct of poor patientprovider communication.…”
mentioning
confidence: 99%
See 1 more Smart Citation